Inhibition of sumoylation prevents experimental fibrosis - Khodzhigorova, Aisa; Distler, Alfiya; Lang, Veronika; Dees, Clara; Schneider, Holm; Beyer, Christian; Gelse, Kolja; Distler, Oliver; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2012)
Objectives: Fibrosis is a predominant cause of death in systemic sclerosis (SSc). First epigenetic modifications have recently been shown to contribute to activation of SSc fibroblasts. Here, we investigated inhibition of sumoylation as a novel antifibrotic approach. Methods: Sumoylation was inhibited by siRNA-mediated knockdown of the Small Ubiquitin-like MOdifiers (SUMO) E2-conjugating enzyme Ubc9, which is essential for sumoylation. The effects of knockdown of Ubc9 were analysed in bleomycin-induced dermal fibrosis, and in the model of fibrosis induced by overexpression of a constitutively active TGF-beta receptor type I (TBR). SUMO-1 and phosphorylated Smad3 were detected by immunohistochemistry. Results: Increased staining for SUMO-1 was detected in patients with SSc and in experimental fibrosis. Inhibition of sumoylation exerted potent antifibrotic effects and prevented dermal thickening, myofibroblast differentiation and accumulation of collagen induced by bleomycin, or by overexpression of constitutively active TBR. Moreover, knockdown of Ubc9 reduced the accumulation of phosphorylated Smad3 in experimental fibrosis indicating that inhibition of sumoylation may normalise canonical TGF-β signalling in vivo. Conclusions: We demonstrate that inhibition of sumoylation reduces canonical TGF-β signalling and prevents experimental fibrosis in different preclinical models. These data provide first evidence that targeting of aberrant sumoylation may be a novel therapeutic approach for fibrotic diseases.
CRIS-Team Scopus Importer:2020-07-01